(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
Perfect detection of estrus is crucial for good husbandry practice of cow. Estrus synchronization is the alternative strategy to bypass the critical problem of estrus detection. Synchronization program allows fixed timed artificial inseminations (FTAI) to evade the estrus detection. The most recently developed programs include protocols for re-synchronization following first or subsequent inseminations. These re-synchronization protocols may involve selected forms of hormonal intervention during the diestrus and pro-estrus periods following FTAI, or following pregnancy diagnosis by ultrasound from 28 days after FTAI. Almost all programs involve strategically timed treatment of prostaglandin F2? (PGF) and gonadotropin releasing hormone (GnRH). Treatment of an estradiol ester and progesterone supplementation per vaginum may be included in some programs. The basic program is the Ovsynch regimen. This mini-review discusses a number of key points related to external hormonal stimulation on ovarian follicular wave to improve pregnancy rate following timed AI. http://dx.doi.org/10.5455/javar.2015.b45